Evaluasi Kebijakan Usaha Kesehatan Sekolah (UKS) Terkait Sarana Air Minum dan Konsumsi Air Putih Siswa Sekolah Dasar Muhammadiyah 2 Surakarta - Muhammad Irfaan Agustian; Setyaningrum Rahmawaty (Yayasan Literasi Sains Indonesia, 2026)
The School Health Program (Usaha Kesehatan Sekolah/UKS) plays a strategic role in promoting healthy behaviors among students, including adequate water consumption. However, its implementation has not fully succeeded in establishing consistent drinking habits. This study aimed to evaluate the implementation of the School Health Program in relation to the adequacy of water consumption among fifth-grade students at SD Muhammadiyah 2 Surakarta. A descriptive study with a mixed-methods approach was employed. Participants included students, teachers, and school stakeholders. Data were collected through observation, interviews, and measurement of water intake based on individual fluid requirements adjusted for body weight. Data were analyzed using descriptive quantitative and qualitative approaches. The findings revealed that 85% of students achieved adequate water intake, while 15% were categorized as inadequate. Despite this, the program implementation was not optimal, as indicated by the absence of structured habituation, lack of continuous monitoring, and limited teacher involvement in shaping drinking behaviors In conclusion, although most students met their fluid requirements, the School Health Program has not been effective in fostering consistent water consumption behavior. Strengthening behavioral-based interventions is essential to improve program effectiveness.